2021
DOI: 10.3390/su13105668
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy Matchmaking Framework for Future Marketplace Deployment

Abstract: Online marketplaces enable cooperation between potential stakeholders by supporting offer and demand identification at the secondary raw material markets. The use of marketplaces facilitates communication between supply chain actors operating within the same or different industry sectors and enables detection of ways to close the loop of their products. This research investigated which criteria to use for the circular cooperation matching of companies in the context of a marketplace. These criteria were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…In this section, the methodology that led to the design of the conceptual framework, applied in this study is presented briefly. This research work is an expansion of the CE matchmaking framework proposed by [7] to IS. A non-systematic, targeted literature search was performed to appropriately address the topic of IS, utilizing among others, papers and knowledge gained during preparation of a previously performed by our team systematic literature review [8], for the adjustment of the CE matchmaking framework for IS.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, the methodology that led to the design of the conceptual framework, applied in this study is presented briefly. This research work is an expansion of the CE matchmaking framework proposed by [7] to IS. A non-systematic, targeted literature search was performed to appropriately address the topic of IS, utilizing among others, papers and knowledge gained during preparation of a previously performed by our team systematic literature review [8], for the adjustment of the CE matchmaking framework for IS.…”
Section: Methodsmentioning
confidence: 99%
“…A non-systematic, targeted literature search was performed to appropriately address the topic of IS, utilizing among others, papers and knowledge gained during preparation of a previously performed by our team systematic literature review [8], for the adjustment of the CE matchmaking framework for IS. For the design of level A of the framework, a set of questions targeting the stakeholders' adoption level of IS practices was developed according to identified studies employing questionnaires related to IS [2], [7], [9]- [11]. For the selection of the benchmarks used within the proposed framework, studies deliberating on matchmaking criteria were identified and further utilized in the design of levels B and C [2], [5], [6], [10], [12]- [14].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations